Mortage finance impediments in egypt: borrowers' perspective - Stefanos, Mina (AUC Knowledge Fountain, 2015)
Mortgage finance is a very powerful financial tool that is considered an essential driver in the economies of almost all countries. Its importance is derived from the fact that it affects one of the basic essential needs of humans which is shelter or home. Mortgage finance is an integral financial tool of developed economies such as the US and is an essential boosting ingredient for developing economies such as Egypt. Although Egypt has been taking serious measures towards establishing a solid mortgage finance market since 2001 through multiple legislative and financial decisions, yet many impediments still hinder the progress of this market keeping it sluggish with almost no significant presence. Legal and financial constraints are among the top factors negatively affecting mortgage finance in Egypt. Although the government has been taking serious steps towards pushing forward this market, both potential lenders and borrowers refrain to join it where each has plausible reasons to do so. This thesis mainly focuses on the borrowers’ side and the various impediments they face. The core part of this thesis is to present to emphasize the relation between certain attributes of potential borrowers and their willingness to acquire a mortgage loan. Borrowers in Egypt are either unaware of the mortgage finance tool as a valid and safe source of property funding or they are reluctant to use it due to its complicated process cycle and high interest rate. The government along with lenders in Egypt should work together to eliminate the various obstacles hindering the progress of such market such as legislating a proper foreclosure scheme. In addition, they should work more towards targeting the correct segment as a start which are low to medium potential homebuyers.